Cracking in Flexural High-Strength Concrete Elements Subjected to Variable Load - Toni Arangjelovski (University "Ss. Cyril and Methodius", Faculty of Civil Engineering Skopje, 2019)
In this paper the influence of loading histories, including variable (imposed) actions, on the behavior of high-strength reinforced concrete beams were analyzed especially the crack parameters: crack width and crack distance. For the evaluation of long-term effects (effects due to creep and shrinkage in concrete structures), quasi-permanent combination of actions was used to verify the serviceability reversible limit state. Extensive experimental program was performed in order to define the factor ψ2 for the evaluation of serviceability reversible limit state for crack control with two specific loading histories. Loading histories are consisted of sustained permanent action G and repeated variable load Q applied in cycles loading and unloading for 24 and 48 hours respectively for the beams series D and E. A total of four reinforced concrete beams, dimensions 15/28/300cm were tested. The beams were made of concrete class C60/75. Experimental results obtained during testing of the beams, from measured maximum crack spacing and crack width, were analyzed by the crack control models given in EN1992-1-1 Eurocode 2 and in the fib Model Code for Concrete Structures 2010.
Keywords: high-strength concrete, crack width, crack spacing, variable load, ψ2 quasi permanent coefficient.